KEANEKARAGAMAN FITOPLANKTON DI PERAIRAN PANTAI SEKITAR MERAK BANTEN DAN PANTAI PENET LAMPUNG - Sri Handayani; Imran SL Tobing (VIS VITALIS Jurnal Ilmiah Biologi, 2008)
A study of phytoplankton diversity in coastal territorial water of Merak, Banten and Penet Lampung were using sub sampling method. The sample was taken from defined stations. The value diversity index and equitabiliity index asses both area showed value which high relative. This indicated that territorial water of both area still competent to support life of phytoplankton. Phytoplankton species coastal territorial water community found are Bacillariophyta and Pyrrophyta.